Analysis of Items for Measuring Technological Literacy Using the Rasch Model - Jumini, Sri; Madnasri, Sutikno; Cahyono, Edy; Md Nadrah, Yatim; Hamzah, H; Fatiatun, F (Universitas Negeri Semarang, 2024)
This research aims to describe the results of the analysis of the quality of the test items for technological literacy skills using the Rasch model from the aspects of validity, reliability, and level of difficulty of the questions. This research uses a descriptive quantitative approach, with construction design and validation. Data was obtained through a test method in the form of 15 multiple-choice questions and a questionnaire with 40 questions. The test was carried out on 6th-semester physics students with an integrated science course totaling 30 students. Data analysis was carried out by describing the results of data processing using the Rasch Model with Winsteps software. The research results showed that the quality of the items on the instrument measuring technological literacy in the validity aspect contained 7 valid questions, and 6 invalid questions regarding knowledge. Meanwhile, 36 questions about attitude measurement were valid and 4 questions were invalid. In the reliability aspect for knowledge questions, the reliability item value is 0.93 in the very good category. Meanwhile, in the attitude questionnaire, the item reliability value was 0.98 in the special category. In terms of the level of difficulty of the questions, for knowledge questions, there are 2 easy questions, 5 medium, 5 difficult, and 3 very difficult. In the very difficult question category, only students with high abilities can answer. For attitude questions, there are 7 easy questions, 14 medium, 9 difficult, and 10 very difficult questions. It can be concluded that this technological literacy test item is suitable for use in assessing technological literacy competency so that it can contribute to measuring technological literacy which has not been done much.